Attenuation of methamphetamine seeking by the mGluR2/3 agonist LY379268 in rats with histories of restricted and escalated self-administration - Kufahl, Peter R. (2012)
Recent findings implicate group II metabotropic glutamate receptors (mGluR(2/3)) in the reinforcing effects of psychostimulants and have identified these receptors as potential treatment targets for drug addiction. Here, we investigated the effects of mGluR(2/3) stimulation on cue- and drug-primed reinstatement in rats with different histories of methamphetamine (METH) self-administration training, under two conditions: 16 daily sessions of short access (90 min/day, ShA), or 8 daily sessions of short access followed by 8 sessions of long access (6 hr/day, LgA). Following self-administration and subsequent extinction training, rats were pretreated with the selective mGluR(2/3) agonist LY379268 (variable dose, 0 – 3 mg/kg), exposed to METH-paired cues or a priming injection of METH (1 mg/kg), and tested for reinstatement of METH-seeking behavior. LgA rats self-administered greater amounts of METH during the second half of training, but when pretreated with vehicle, ShA and LgA rats showed cue- and drug-primed reinstatement at equivalent response rates. However, LgA rats demonstrated greater sensitivity to mGluR(2/3) stimulation with attenuated responding during cue-induced reinstatement after 0.3 mg/kg and higher doses of LY379268, whereas ShA rats decreased cue-induced reinstatement behavior following 1.0 mg/kg and 3.0 mg/kg LY379268. Additionally, both LgA and ShA rats exhibited decreased METH-primed reinstatement behavior following 0.3 mg/kg and higher doses of LY379268. A separate group of control rats was trained to self-administer sucrose pellets, and demonstrated attenuated cue-induced sucrose-seeking behavior following 1.0 and 3.0 mg/kg LY379268. Together, the results indicate that LY379268 has differential attenuating effects on cue-induced reinstatement behavior in rats with different histories of METH intake.